2021
DOI: 10.1111/eci.13542
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of macrovascular invasion in hepatocellular carcinoma

Abstract: Background and aims In patients with hepatocellular carcinoma (HCC), macrovascular invasion (MaVI) limits treatment options and decreases survival. Detailed data on the relationship between MaVI extension and patients' characteristics, and its impact on patients' outcome are limited. We evaluated the prevalence and extension of MaVI in a large cohort of consecutive HCC patients, analysing its association with liver disease and tumour characteristics, as well as with treatments performed and patients' survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(41 reference statements)
0
15
1
Order By: Relevance
“…The presence and extension of vascular invasion along with the performance status and ascites have a significant impact on patient survival and the choice of therapeutics. 49 With the presence of aforementioned factors and most treatments being contraindicated in this setting, these patients perform poor with lower median OS of 2-4 months after best supportive care (BSC). 50…”
Section: Risk Factors For Pvtt Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence and extension of vascular invasion along with the performance status and ascites have a significant impact on patient survival and the choice of therapeutics. 49 With the presence of aforementioned factors and most treatments being contraindicated in this setting, these patients perform poor with lower median OS of 2-4 months after best supportive care (BSC). 50…”
Section: Risk Factors For Pvtt Formationmentioning
confidence: 99%
“…Although the selection of the treatment modality plays a significant role, it's also imperative to know that vessel involvement itself has a central role in possible progression and prognosis of the HCC in these patients. 49,151 A nation-wide survey by the Liver Cancer Study Group of Japan reported survival benefits for LR in HCC patient with PVTT. 152 Patients were divided into a LR group (n=2,093) and a non-LR group (received treatment TACE, ablation, chemotherapy, BSC, and other treatments).…”
Section: Surgery -Liver Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, a more weight was observed for bilirubin, but despite this the Pre-TACE-Predict model underestimated, thus tumour features probably affect prognosis more than liver function tests. All in all, we feel that the lower weight attributed by the recalibrated model to macroscopic vascular invasion and aetiology of liver disease might more closely reflect the population of patients who in the future will be treated with TACE, as the widespread treatment of HCV patients with DAA will likely equalize this variable by avoiding the risk of death due to liver decompensation following successful oncological treatment, while the advent of other therapeutic options with competitive overall survival rates and a lower likelihood of posttreatment hepatic decompensation-such as trans-catheter arterial radio-emobolization and new systemic treatments-will decrease the proportion of patients with macroscopic vascular invasion undergoing TACE [30][31][32][33]. With the exception of aetiology and macrovascular invasion, the remaining prognostic factors (multiplicity, size, AFP, albumin and bilirubin) are present even in the m-HAP-III model.…”
mentioning
confidence: 99%